On Hypothesis of the Existence of Superfine Fluid that Producing Electromagnetic Field - Bintang A.S. W.A.M; E Amalia; D Sardjadi (Institut Teknologi Bandung, 2020)
Based on previous work of reformulation of equation for compressible fluid flow by analogy with Maxwell equation, further effort is successfully done to show similarity between governing equations for continuum, incompressible, non-viscous fluid flow and Maxwell equation for homogeneous medium without electric charge and without magnetic pole. From mathematical analysis of both system of equations, impulse vector in fluid field is equivalent with electric field in electromagnetic field, vorticity in fluid field is equivalent with magnetic fields in electromagnetic field, and speed of sound in fluid field is equivalent with speed of light in electromagnetic field. The success of finding the similarity leads to a hypothesis about the existence of a “superfine fluid” that forming background field in universe that having a characteristic similar with fluid field which is continuum, incompressible and inviscid